Pengaruh Sop, Knowledge Sharing, dan Leadership terhadap Efektivitas Pencapaian KPI ( Studi Kasus pada Karyawan PT Gracia Utamajaya) - Bayu Indra Laksana; Bambang Sutejo (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of Standard Operating Procedures (SOPs), knowledge sharing, and leadership on the effectiveness of Key Performance Indicators (KPIs) achievement among employees at PT Gracia Utamajaya. The research method used was a quantitative census approach, with the entire population of 82 employees serving as respondents. Primary data was collected through questionnaires and analyzed using multiple linear regression analysis using SPSS version 26 software. The results also included instrument validity and reliability tests. The results indicate that SOPs, knowledge sharing, and leadership simultaneously significantly influence KPI achievement. Partially, knowledge sharing had a positive and significant effect on KPIs, while SOPs and leadership showed a significant negative effect, indicating that overly rigid SOP implementation and a less adaptive leadership style can hinder the effectiveness of KPI achievement. The conclusion is that improving KPI achievement at PT Gracia Utamajaya is more effectively driven by strengthening a knowledge sharing culture, accompanied by adjusting SOP implementation and leadership style to be more flexible, innovative, and in line with the company's operational dynamics.   Keywords: SOP, Knowledge Sharing, Leadership, KPI, Employee Performance